Ancient Introgression Between Distantly Related White Oaks (Quercus sect. Quercus) Shows Evidence of Climate-Associated Asymmetric Gene Exchange. (11th September 2021) - O'Donnell, Scott T; Fitz-Gibbon, Sorel T; Sork, Victoria L
Abstract: Ancient introgression can be an important source of genetic variation that shapes the evolution and diversification of many taxa. Here, we estimate the timing, direction, and extent of gene flow between two distantly related oak species in the same section ( Quercus sect. Quercus ). We estimated these demographic events using genotyping by sequencing data, which generated 25 702 single nucleotide polymorphisms for 24 individuals of California scrub oak ( Quercus berberidifolia ) and 23 individuals of Engelmann oak ( Quercus engelmannii ). We tested several scenarios involving gene flow between these species using the diffusion approximation-based population genetic inference framework and model-testing approach of the Python package DaDi. We found that the most likely demographic scenario includes a bottleneck in Q. engelmannii that coincides with asymmetric gene flow from Q. berberidifolia into Q. engelmannii . Given that the timing of this gene flow coincides with the advent of a Mediterranean-type climate in the California Floristic Province, we propose that changing precipitation patterns and seasonality may have favored the introgression of climate-associated genes from the endemic into the non-endemic California oak.